Effectiveness Leadership and Optimalization of Local Potential in Nutrition Status Improvement Effort (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Indonesia which is a developed country, has community health issue, as nowadays face a double concern of nutrition problem. Based on the data in 2007 to 2010, over nutrition prevalence on children under five years was 14.0%, increase from condition in 2007 which was 12.2%, aligned with poor and malnutrition prevalence. Programs applied has not resulted nutrition status improvement as expected. The problem in this research is how does the effectiveness of community empowerment optimalization model in the effort to improve nutrition status. Qualitative approach is used to evaluate model implementation, with focus of the research is model implementation based on the input, process and output. Respondents are determined by purposive technique. While the instruments are observation guide, interview guide, and FGD guide. Analysing Technique by Miles and Huberman model. The quantitative approach, to assess model effectiveness, with data-fill form intrument. The calculation is viewed from number increase and effectiveness criteria from Sugiyono. Local potential optimalization in the effort to improve nutrition status indicate effectiveness criteria (60%), This activity could not result maximum effectiveness level due to the leadership style tends to paternalistic which is dominated by otoritarism, causing community empowerment by cadre members and Family Welfare Program which are the potential that will be utilized can play maximum role.